Investigating the Impacts of Customer Satisfaction on Firm Performance - Lianny Leo; Lindawati Gani; Johnny Jermias (Gadjah Mada International Journal of Business, 2009)
The purpose of this study is to investigate the impact of customer satisfaction on firm performance. We argue that a firm’s financial performance will be positively affected by its ability to satisfy its customers. By satisfying its customers, a firm increases its ability to acquire new customers, retain existing customers, and increase customer profitability. Based on sample of firms listed on the Indonesian Stock Exchange, we hypothesize and find that customer satisfaction is positively and significantly related to firm performance in terms of return on assets and market value of equity. These findings are consistent with the view that customer satisfaction is a leading indicator of financial performance.